Zn3 (OH) 2V2O72H2O-coated C3N4 zinc ion battery positive electrode material and preparation method thereof
By constructing the heterostructure of Zn3(OH)2V2O7·2H2O and carbon nitride and using in-situ electrochemical activation technology, the problems of low conductivity and ion mobility of the positive electrode material of zinc ion battery are solved, and high capacity, excellent rate performance and long cycle life are achieved.
Patent Information
- Application Number
- CN202411596616.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing zinc ion battery positive electrode materials limit their theoretical capacity due to their low conductivity and ion mobility, and the structure is prone to collapse during deep charging and discharge, affecting the cycling performance.
By constructing a heterostructure, Zn3(OH)2V2O7·2H2O is combined with carbon nitride, and in-situ electrochemical activation technology is used to improve the zinc adsorption capacity and conductivity of the material.
The conductivity and ion diffusion rate of the positive electrode material of zinc ion battery are significantly improved, and capacity, rate performance and cycle stability are improved.
Smart Images

Figure CN119650613A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to a Zn3(OH)2V2O7·2H2O@C3N4 zinc ion battery positive electrode material and a preparation method thereof. Background Art
[0002] In the face of the global demand for carbon emission reduction, the development of safe and environmentally friendly energy storage equipment has become an important issue in the energy field. Aqueous zinc-ion batteries have become a potential alternative to lithium-ion batteries due to their high safety and cost advantages.
[0003] Among the existing zinc ion positive electrode materials, vanadium-based positive electrode materials have attracted much attention due to their open structure, high theoretical capacity, diverse crystal structure and high pseudocapacitance. However, due to their inherent low conductivity and ion mobility characteristics, they are often limited in their full theoretical capacity. In addition, the large hydration radius of Zn2+ during deep charge and discharge may cause the collapse of the positive electrode structure, thereby affecting its cycle performance. It is necessary to find a suitable modification method to improve the electron / ion dynamics of the vanadium-based positive electrode to promote the increase in capacity, and at the same time adjust its crystal structure, such as introducing vacancies, coating with a carbon layer, forming a composite heterostructure and other strategies to slow down the destruction of the material during the charge and discharge cycle.
[0004] At the same time, the positive electrode materials of zinc-ion batteries often face problems such as large zinc ion migration resistance and low diffusion rate during the cycle process, which limits the overall performance of the battery. Summary of the invention
[0005] Purpose of the invention: The first purpose of the present invention is to provide a positive electrode active material composed of a complex of V2O3 and C3N4. The second purpose of the present invention is to provide a method for preparing the above-mentioned positive electrode active material. The third purpose of the present invention is to provide a Zn3(OH)2V2O7·2H2O@C3N4 zinc ion battery positive electrode material which can improve the conductivity and ion diffusion rate of the positive electrode, thereby simultaneously improving the capacity, rate performance and cycle stability. The fourth purpose of the present invention is to provide a method for preparing the above-mentioned zinc ion battery positive electrode material.
[0006] Technical solution: The method for preparing the positive electrode active material provided by the present invention comprises the following steps:
[0007] (1) fully dissolving vanadium oxide in a solvent, adding carbon nitride g-C3N4 and stirring and mixing, and drying the obtained solution to obtain a solid powder;
[0008] (2) The solid powder is calcined, and the resulting V2O3 and C3N4 composite is the positive electrode active material.
[0009] Furthermore, in step (1), the preparation method of the carbon nitride g-C3N4 is: placing a carbon nitride precursor in a muffle furnace, heating the temperature to 500-600°C at a heating rate of 5-10°C / min and keeping it warm for 1-2h, to obtain the carbon nitride precursor; the carbon nitride precursor includes urea, dicyandiamide or melamine.
[0010] Furthermore, in step (1), the vanadium oxide is vanadium pentoxide; the usage ratio of V2O3 to CN is 4mmol:0.2-1g, preferably 4mmol:0.4-0.6g; and the solvent is a hydrogen peroxide solution with a mass concentration of 1-2wt%.
[0011] Furthermore, in step (2), the calcination treatment conditions are: in an inert atmosphere, heating to 500-650° C. at a heating rate of 5-10° C. / min and keeping the temperature for 1-3 hours.
[0012] The preparation method of the positive electrode material of Zn3(OH)2V2O7·2H2O@C3N4 zinc ion battery provided by the present invention comprises the following steps:
[0013] (11) mixing the above-mentioned positive electrode active material, conductive agent and adhesive into slurry, then coating the slurry on the current collector, vacuum drying, and assembling a zinc ion battery in the manner of positive electrode sheet, separator, dripping electrolyte and negative electrode zinc sheet;
[0014] (12) The zinc ion battery is activated in situ and charged to a voltage of 1.7-2.0 V in the first cycle, at which the positive electrode active material is promoted to undergo a structural phase change into a Zn3(OH)2V2O7·2H2O@C3N4 complex, thereby obtaining a Zn3(OH)2V2O7·2H2O@C3N4 zinc ion battery positive electrode material.
[0015] Furthermore, in step (11), the conductive agent is superP, carbon black or acetylene black.
[0016] Furthermore, in step (11), the electrolyte is a zinc trifluoromethanesulfonate electrolyte with a concentration greater than 2 mol / L.
[0017] Furthermore, in step (12), the current of the first cycle charging is ≥ 0.5A g -1 If the current is less than this value, the phase change cannot occur.
[0018] Principle of invention: The present invention develops a Zn3(OH)2V2O7·2H2O@C3N4 zinc ion battery positive electrode material, which significantly improves the electrochemical performance of the material by constructing a heterogeneous structure and adopting in-situ electrochemical activation technology.
[0019] In the synthesis process of the present invention, a heterostructure construction method is used to combine Zn3(OH)2V2O7·2H2O with carbon nitride. This heterostructure not only improves the zinc adsorption capacity of the material, but also reduces the migration energy barrier of zinc ions, thereby accelerating the diffusion rate of zinc ions. At the same time, through the in-situ electrochemical activation process, the material can adaptively change its structure during the charge and discharge process, improve the conductivity and enhance the kinetic performance of the electrochemical reaction. The results show that the positive electrode material has a strong zinc adsorption capacity, a lower zinc migration energy barrier and excellent conductivity, providing an efficient solution for improving the performance of zinc ion batteries.
[0020] The method for quantitatively preparing high-performance Zn3(OH)2V2O7·2H2O@C3N4 provided by the present invention is based on first successfully preparing a V2O3@C3N4 precursor by a thermal solid-state reduction method, and then using the precursor as an active material to prepare a soft-pack or button battery and charge it to a certain voltage to achieve in-situ phase transformation of a large number of positive electrode materials to obtain a high-performance Zn3(OH)2V2O7·2H2O@C3N4 vanadium oxide composite positive electrode material.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The positive electrode active material V2O3@C3N4 of the present invention adopts a calcination method, and the preparation method is simple and suitable for large-scale production; (2) The in-situ activation process only requires charging the prepared battery to a certain voltage, without the need for cumbersome and complicated material preparation processes, and does not involve hazardous chemical reagents and special chemical reaction equipment. The process operation is simple and safe; (3) The positive electrode material of the zinc ion battery obtained by the present invention has excellent performance: high capacity, at 0.5A g -1 At a current density of 518.5 mAh g -1 Specific capacity; excellent rate performance and long cycle life, at 20Ag -1 After 3800 cycles at the same current density, there is still 208.3 mAh g -1 Specific capacity (capacity retention rate 86.7%). BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD diagram of V2O3@C3N4 prepared in Example 3, Example 5 and Comparative Example 1;
[0023] Figure 2 This is a graph of the positive electrode rate performance of Zn3(OH)2V2O7·2H2O@C3N4-0 / 0.2 / 0.4 / 0.6 / 0.8 / 1.0 prepared in Examples 1-5 and Comparative Example 1;
[0024] Figure 3This is a cycle performance diagram of Zn3(OH)2V2O7·2H2O@C3N4 prepared in Example 8 and Example 10 at 20A / g;
[0025] Figure 4 This is a non-in-situ high-resolution transmission image of the Zn3(OH)2V2O7·2H2O@C3N4-0.6 cathode material in Example 8 at a voltage of 0.2 V in the 15th cycle;
[0026] Figure 5 It is the charging GCD diagram at 0.2A / g current in Comparative Example 3;
[0027] Figure 6 This is a cycle performance diagram of a soft-pack battery with an enlarged loading amount of the Zn3(OH)2V2O7·2H2O@C3N4 positive electrode in Example 11;
[0028] Figure 7 This is a diagram of the actual application of the soft-pack battery prepared with Zn3(OH)2V2O7·2H2O@C3N4 as the positive electrode under increased loading capacity in Example 11. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with specific embodiments and drawings.
[0030] Example 1: The positive electrode active material V2O3 and C3N4 composite provided in this example is prepared by the following method:
[0031] (1) Weigh 20 g of urea and place it in a muffle furnace, heat it to 550 °C at a heating rate of 5 °C / min and keep it at that temperature for 1 h to obtain powdered carbon nitride (g-C3N4);
[0032] (2) Dissolve 4 mmol of vanadium pentoxide in 10 ml of 1.5 wt.% hydrogen peroxide solution. After the mixture is completely dissolved, add 0.2 g of carbon nitride. Stir continuously for 10 h and then place the beaker in a forced air drying oven at 80° C. in an air atmosphere for 12 h until the mixture is completely dry.
[0033] (3) The mixture was then transferred to a mortar and ground into powder particles, which were then placed in a tubular furnace and heated to 550°C at a heating rate of 5°C / min under an argon atmosphere and kept warm for 1 h. The resulting black powder was the positive electrode active material V2O3@C3N4-0.2 (0.2 represents the mass of the added carbon nitride).
[0034] Example 2: The difference from Example 1 is that in step (2), the ratio of vanadium pentoxide to carbon nitride is 4 mmol:0.4 g, and the positive electrode active material V2O3@C3N4-0.4 is obtained.
[0035] Example 3: The difference from Example 1 is that in step (2), the ratio of vanadium pentoxide to carbon nitride is 4 mmol:0.6 g, and the positive electrode active material V2O3@C3N4-0.6 is obtained.
[0036] Example 4: The difference from Example 1 is that in step (2), the ratio of vanadium pentoxide to carbon nitride is 4 mmol:0.8 g, and the positive electrode active material V2O3@C3N4-0.8 is obtained.
[0037] Example 5: The difference from Example 1 is that in step (2), the ratio of vanadium pentoxide to carbon nitride is 4 mmol:1 g, and the positive electrode active material V2O3@C3N4-1 is obtained.
[0038] Comparative Example 1: The difference from Example 1 is that step (1) is not included, the amount of carbon nitride used is 0, and the positive electrode active material V2O3@C3N4-0 is obtained.
[0039] The XRD patterns of the positive electrode active material V2O3@C3N4-0.6 prepared in Example 3 and the positive electrode active material V2O3@C3N4-1 prepared in Example 6 are shown in FIG. Figure 1 shown. Figure 1 The samples include carbon nitride with addition amounts of 0, 0.6, and 1.0 gs, respectively; from the analysis description, it can be seen that when carbon nitride is added to the raw material, the vanadium oxide obtained is based on the V2O3 crystal form (corresponding to the standard PDF card: 4-4-2833), but if no carbon nitride is added, the product obtained is still V2O5 (corresponding to the standard PDF card: 4-5-4335), which also shows that the carbon nitride in the raw material plays the role of a reducing agent.
[0040] Embodiment 6: The preparation method of Zn3(OH)2V2O7·2H2O@C3N4 zinc ion battery positive electrode material provided in this embodiment comprises the following steps:
[0041] (1) Weigh 1.4 g of the positive electrode active material V2O3@C3N4-0.2 prepared in Example 1, 0.4 g of superP, and 10 mL of 20 mg / LPVDF solution and stir for 12 h to prepare a slurry. Use a 120 mm scraper to coat the slurry on a 0.05 mm titanium foil, then transfer it to a vacuum drying oven and dry it at 80 ° C for 12 h to obtain a loading of 1.0 g / cm 2 Positive electrode;
[0042] (2) Cut the positive electrode sheet into a circular button battery positive electrode with a diameter of 12 mm, select 3 mol / L zinc trifluoromethanesulfonate as the electrolyte, 0.1 mm zinc sheet as the negative electrode, and glass fiber membrane as the separator to prepare a CR2032 button battery;
[0043] (3) The prepared button cell can be directly activated in situ and its electrochemical performance tested on a CT-4008T-164. The first cycle current is set to 0.5 A / g and the charging voltage is cut off to 1.8 V. Under the activation conditions, the structural phase transformation of the positive electrode active material is promoted to a Zn3(OH)2V2O7·2H2O@C3N4 complex.
[0044] Example 7: The difference from Example 6 is that the positive electrode active material in step (1) is V2O3@C3N4-0.4 prepared in Example 2.
[0045] Example 8: The difference from Example 6 is that the positive electrode active material in step (1) is V2O3@C3N4-0.6 prepared in Example 3.
[0046] Example 9: The difference from Example 6 is that the positive electrode active material in step (1) is V2O3@C3N4-0.8 prepared in Example 4.
[0047] Example 10: The difference from Example 6 is that the positive electrode active material in step (1) is V2O3@C3N4-1 prepared in Example 5.
[0048] Comparative Example 2: The difference from Example 6 is that the positive electrode active material in step (1) is V2O3@C3N4-0 prepared in Comparative Example 1.
[0049] Comparative Example 3: The difference from the embodiment is that in step (3), the first-cycle current is set to 0.2 A / g.
[0050] Figure 2 The button cells prepared in Examples 6 to 10 and Comparative Example 2 with Zn3(OH)2V2O7·2H2O@C3N4 as the positive electrode material have rate performance at different currents, and the charge and discharge range is 0.2-1.8V. Among them, the best sample Zn3(OH)2V2O7·2H2O@C3N4-0.6 has a charge and discharge performance of 0.5A g -1 At a current density of 518.5 mAh g -1 Specific capacity.
[0051] Figure 3 The cycle performance diagram of the button cells in Example 8, Example 10 and Comparative Example 2. The button cell prepared in Example 8 with Zn3(OH)2V2O7·2H2O@C3N4-0.6 as the positive electrode material is -1 After 110 cycles at the same current density, there is still 407.1 mAh g -1 Specific capacity (capacity retention rate 80.3%); at 20Ag -1After 3800 cycles at the same current density, there is still 208.3 mAh g -1 When the amount of carbon nitride added is 0, that is, V2O5 crystal form, the corresponding data is: 0.5A g -1 After 110 cycles at the current density of 83.1 mAh g -1 Specific capacity (capacity retention rate 34.0%), 20A g -1 The current density has no capacity. This is because the material has poor rate performance and cannot support charging and discharging at high currents. When the corresponding carbon nitride addition amount is 1, the corresponding Zn3(OH)2V2O7·2H2O@C3N4-1.0 sample: 0.5A g -1 After 110 cycles at the current density, there is 124.2 mAh g -1 Specific capacity (capacity retention rate 22.8%), 20A g -1 After 3800 cycles at the current density, there is 105.7 mAh g -1 This also shows that it is necessary to select an appropriate amount of carbon nitride addition, as excessive carbon nitride addition will inhibit the performance of the product.
[0052] Figure 4 This is a non-in-situ high-resolution transmission image of the Zn3(OH)2V2O7·2H2O@C3N4-0.6 positive electrode material in Example 8 after 15 cycles at a voltage of 0.2V. In this image, the lattice fringes of Zn3(OH)2V2O7·2H2O and low-crystallinity g-C3N4 can be seen, and there is an obvious interface between the two composite materials, which proves the formation of the heterojunction.
[0053] Figure 5 The GCD diagram of the charge at 0.2A / g current in Comparative Example 3 is shown in FIG. Figure 5 It can be seen that at a current of 0.2A / g, the voltage remains at 1.34V, indicating that the voltage cannot be charged up and that greater energy (i.e., greater current) is required from the outside to induce phase change.
[0054] Example 11: The preparation method of the high-load Zn3(OH)2V2O7·2H2O@C3N4 positive electrode soft pack battery provided in this example comprises the following steps:
[0055] (1) Weigh 14 g of the positive electrode active material V2O3@C3N4-0.6 and 4.0 g of super P prepared in Example 3, and stir 100 mL of 20 mg / LPVDF solution for 12 h to prepare a slurry. Use a 500 mm scraper to coat the slurry on a 0.05 mm titanium foil, then transfer it to a vacuum drying oven and dry it at 80 ° C for 12 h to obtain a loading of 5.0 g / cm 2Positive electrode;
[0056] (2) Cut the positive electrode sheet into a rectangular battery positive electrode sheet with a length and width of 3*2 cm respectively, select 3 mol / L zinc trifluoromethanesulfonate as the electrolyte, 0.1 mm zinc sheet as the negative electrode, glass fiber membrane as the separator, and polyethylene film as the battery shell to prepare a transparent soft-pack battery;
[0057] (3) The prepared soft-pack battery can also be directly activated and electrochemically tested on the Xinwei (CT-4008T-164). By setting the first cycle current to 0.5 A / g and the charging voltage to 1.8 V, a high-load Zn3(OH)2V2O7·2H2O@C3N4 positive electrode soft-pack battery is obtained.
[0058] Figure 6 This is the cycle performance diagram of the soft pack battery prepared in Example 11 with Zn3(OH)2V2O7·2H2O@C3N4 as the positive electrode material. -1 After 110 cycles at the same current density, there is still 371 mAh g -1 Even after 270 cycles, it can still be charged and discharged normally, and the discharge specific capacitance is still 203.9mAh g -1 .
[0059] Figure 7 This is a practical application diagram of the soft-pack battery prepared in Example 11 with Zn3(OH)2V2O7·2H2O@C3N4 as the positive electrode material. The soft-pack batteries prepared under different bending conditions: 0°, 45°, 90°, and 180° can effectively light up LED lights; two series-connected boost soft-pack batteries can successfully power a mobile phone.
Claims
1. A method for preparing a positive electrode active material, characterized in that: The following steps are involved: (1) fully dissolving vanadium oxide in a solvent, adding carbon nitride g-C3N4 and stirring and mixing, and drying the obtained solution to obtain a solid powder; (2) The solid powder is calcined, and the resulting V2O3 and C3N4 composite is the positive electrode active material.
2. The preparation method according to claim 1, characterized in that: In step (1), the preparation method of the carbon nitride g-C3N4 is: placing a carbon nitride precursor in a muffle furnace, heating it to 500-600°C at a heating rate of 5-10°C / min and keeping it warm for 1-2h, to obtain the carbon nitride precursor; the carbon nitride precursor includes urea, dicyandiamide or melamine.
3. The preparation method according to claim 1, characterized in that: In step (1), the vanadium oxide is vanadium pentoxide; the usage ratio of V2O3 to CN is 4mmol:0.2-1g; and the solvent is a hydrogen peroxide solution with a mass concentration of 1-2wt%.
4. The preparation method according to claim 1, characterized in that: In step (2), the calcination treatment conditions are: in an inert atmosphere, heating to 500-650° C. at a heating rate of 5-10° C. / min and keeping the temperature for 1-3 hours.
5. A positive electrode active material obtained by the preparation method according to any one of claims 1 to 4.
6. A method for preparing a positive electrode material for a Zn3(OH)2V2O7·2H2O@C3N4 zinc ion battery, characterized in that: The following steps are involved: (11) The positive electrode active material, conductive agent and adhesive as claimed in claim 5 are mixed into a slurry, and then the slurry is coated on a current collector, and after vacuum drying, a positive electrode sheet, a separator, an electrolyte solution and a negative electrode zinc sheet are assembled into a zinc ion battery; (12) The zinc ion battery is activated in situ and charged to a voltage of 1.7-2.0 V in the first cycle, at which the positive electrode active material is promoted to undergo a structural phase change into a Zn3(OH)2V2O7·2H2O@C3N4 complex, thereby obtaining a Zn3(OH)2V2O7·2H2O@C3N4 zinc ion battery positive electrode material.
7. The preparation method according to claim 6, characterized in that: In step (11), the conductive agent is superP, carbon black or acetylene black.
8. The preparation method according to claim 6, characterized in that: In step (11), the electrolyte is a zinc trifluoromethanesulfonate electrolyte with a concentration greater than 2 mol / L.
9. The preparation method according to claim 6, characterized in that: In step (12), the current of the first charging cycle is ≥ 0.5A g -1 .
10. A Zn3(OH)2V2O7·2H2O@C3N4 zinc ion battery positive electrode material prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Preparation method of negative electrode material Zn<3>(OH)<2>V<2>O<7>.2H<2>O of aqueous zinc ion battery
CN108346795A
Flower-like Zn3(OH)2V2O7.2H2O photocatalyst and preparation method thereof
CN110479243A
Organic ion doped vanadium oxide cathode material for aqueous zinc ion battery and preparation method and application of organic ion doped vanadium oxide cathode material
CN111244422A
V2O3-porous carbon nanofiber supercapacitor electrode material and preparation method thereof
CN111724998A
Zinc ion battery positive electrode material and preparation method and application thereof
CN111785972A